Growth pattern and condition index of exploited Meretrix meretrix (Linnaeus, 1758) at Kambu River estuary, Southeast Sulawesi, Indonesia - Bahtiar, Bahtiar; Purnama, Muhammad Fajar; Baharuddin, La Ode; Findra, Muhammad Nur (Aceh Journal of Animal Science, 2023)
Meretrix meretrixis one of the economical shellfish that has been exploited in Kendari Bay, Indonesia. Several studies have been done, but its growth pattern and condition index are not fully known. This study aims to determine its growth pattern and condition index at the Kambu River estuary, Kendari Bay. This research was conducted for 6 months from August 2021 to January 2022. Clams were collected using a rake, cleaned, and brought to the laboratory to be measured for length and weight using calipers and scales with an accuracy of 0.1 mm and 0.01g, respectively. Furthermore, the clam meat was dried using an oven and weighed. Data on growth and condition index were analyzed using simple regression and the Mann-Whitney test, respectively. The results showed that the growth of M. meretrix was in negative allometric conditions, with b values in males and females in the range of 2.20-3.00 and 1.86-2.73, respectively. The condition index of male and female clam ranged from 1.86-2.62 and 1.66-2.41, respectively, and differed significantly by month. The results of the Mann-Whitney test on clam showed that there was no significant difference between August-November and December-January. In conclusion, male and female clam had relatively different patterns based on the observation period, while the condition index was in the skinny and medium category